APB Research Workshop on Research and Publication / NoorAileen Ibrahim and Nur Fatima Wahida Mohd Nasir - Ibrahim, NoorAileen; Mohd Nasir, Nur Fatima Wahida (Universiti Teknologi MARA, Perak, 2024)
In February of 2024, the Academy of Language Studies or Akademi Pengajian Bahasa (APB) UiTM Perak in association with Research, Industrial Linkages, Community & Alumni Network or Bahagian Penyelidikan, Jaringan Industri, Masyarakat dan Alumni (PJIM&A) organized a research workshop at the Smart Classroom in UiTM Tapah campus. The workshop aims to encourage the APB lecturers to produce high impact and quality publications. Puan Sheema Liza Idris the Ketua Pusat Pengajian (KPP) of APB UiTM Perak, En Mohd Syahir Rani the Coordinator of Tapah campus, Puan Nur Fatima Wahida Mohd Nasir the APB PJIM&A coordinator along with the APB research committee had invited experts in the field of research to share their insights and invaluable knowledge on research and publication.